IbM for increasing youth work productivity in Bojongsari Village - Gelar Budiman; Muhammad Iqbal; Astry Novianty (Berdikari: Jurnal Pengabdian Masyarakat Indonesia, 2018)
Bojongsari Village (Bojongsoang District) is a village located in Bandung regency. The village has a low Human Development Index (HDI). The village has a high open unemployment rate. The village of Bojongsari has a relatively low growth rate of living eligibility (based on data obtained from Bojongsari village). The training for the youths of Karang Taruna in the village of Bojongsari, especially for those who still do not get a job is a solution offered in order to reduce the number of open and underemployed unemployment in the region. The trainings that have been carried out include enhancing the ability to use computers, office applications (word, excel, and powerpoint), and Windows applications and networks in both villages. It is expected that with this training, unemployment will decrease and increase the HDI of both villages. The implementation of community service is evaluated monthly and a roadmap has been developed to improve the HDI of these two villages as a model for other villages in Bandung regency.